Is bigger always better? The effect of size on defaults - Giulio Bottazzi; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
Analyzing a large sample of Italian firms we find that the probability of default increases with size. This contrasts with the common observation, based on measures of exit from business registry data, that firms' death rate is inversely related to the scale of their operation and suggests a rethinking of the economic role of larger companies.
Keywords: 330